Peripheral Clock System Abnormalities in Patients With Parkinson’s Disease - Li, Tianbai; Cheng, Cheng; Jia, Congcong; Leng, Yue; Qian, Jin; Yu, Hang; Liu, Yufei; Wang, Nanxing; Yang, Yuting; Al-Nusaif, Murad; Le, Weidong (Frontiers in Aging Neuroscience, 2021)
Objective: To evaluate the altered expression of peripheral clock genes, circulating melatonin levels, and their correlations with sleep-wake phenotypes including probable rapid eye movement sleep behavior disorder (pRBD) symptoms in a relatively large sample of Parkinson’s disease (PD) patients. Methods: We determined the expression profiles of five principal clock genes, BMAL1, CLOCK, CRY1, PER1, and PER2, in the peripheral blood mononuclear cells (PBMCs) of PD patients (n=326), and healthy controls (HC, n=314) using real-time quantitative PCR. Melatonin concentrations in the plasma of two groups were evaluated by enzyme-linked immunosorbent assay. Then we performed comprehensive association analyses on the PBMCs clock gene expression, plasma melatonin levels and sleep characteristics. Results: Our data showed that the expression levels of BMAL1, CLOCK, CRY1, PER1, and PER2 were significantly decreased in the PBMCs of PD as compared with that of HC (P< 0.05). PD patients had reduced plasma melatonin levels compared with HC (P< 0.0001). pRBD and excessive daytime sleepiness are common in these PD patients and are associated with the expression levels of all five clock genes (r= -0.344~-0.789, P< 0.01) and melatonin concentrations (r= -0.509~-0.753, P< 0.01). Statistical analyses also revealed that a combination of five clock genes and melatonin could reach a high diagnostic performance (areas under the curves, 97%) for PD comorbid pRBD. Conclusions: This case-control study demonstrates that peripheral BMAL1, CLOCK, CRY1, PER1, PER2 and melatonin levels are altered in PD patients and may serve as endogenous markers for sleep and wakefulness disturbances of PD.